Peran Kompetensi SDM BPKN dalam Meningkatkan Perlindungan Konsumen melalui Kualitas Pelayanan Berbasis Etika Bisnis - Antoni Ludfi Arifin; Joko Nugroho (Jurnal Administrasi Publik dan Pemerintahan, 2026)
Consumer protection is a crucial element of modern economic systems as it seeks to maintain a balanced relationship between business actors and society as users of goods and services. BPKN plays a strategic role in providing advocacy, policy recommendations, and strengthening the national consumer protection framework in Indonesia. However, the effectiveness of consumer protection is not solely determined by regulatory frameworks but is also significantly influenced by the quality of human resources responsible for delivering public services. This study aims to analyses the role of BPKN HR competencies in enhancing consumer protection through service quality grounded in business ethics. The research employs a qualitative approach using a literature study method, drawing upon reputable academic journal articles and scholarly sources related to HR competencies, public service quality, and business ethics. The findings indicate that HR competencies constitute a key factor in improving the effectiveness of consumer protection. Public officials possessing technical, analytical, and digital competencies, as well as strong communication and empathetic skills, are better positioned to deliver higher-quality public services. Service quality supported by the dimensions of reliability, responsiveness, assurance, and empathy has been shown to strengthen public trust in consumer protection institutions. Furthermore, the internalization of business ethics within organizations plays a vital role in maintaining integrity, transparency, and accountability in service delivery. The integration of human resource competencies, service quality, and business ethics therefore forms a critical foundation for developing a responsive, credible, and adaptive consumer protection system in the context of an evolving digital economy.